2016
DOI: 10.1016/j.vetmic.2016.04.023
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Isolation and confirmation of viral nervous necrosis (VNN) disease in golden grey mullet (Liza aurata) and leaping mullet (Liza saliens) in the Iranian waters of the Caspian Sea

Abstract: A B S T R A C TThe present study was conducted on 428 moribund mullet fish samples to isolate and identify the causative agent of a mysterious acute mortality which recently occurred in wild mullets in Iranian waters of Caspian Sea, suspected to be due to viral nervous necrosis (VNN) disease. Disease investigation was carried out employing various diagnostic procedures such as virology, bacteriology, parasitology, haematology, histopathology, IFAT, IHC and nested RT-PCR. Brain and eye samples of affected fishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Three years later, it was recorded in European sea bass produced in Martinique (West Indies, France) and French Mediterranean (Breuil et al 1991). Since then, similar clinical signs with encephalitis associated with picorna-like viral particles were observed in the Asian sea bass Lates calcarifer cultured in Australia (Glazebrook et al 1990; Munday et al (2002) 2002), as well as in turbot Scopthalmus maximus (Bloch et al 1991), red-spotted grouper Epinephalus akaara (Nishizawa et al 1995), striped jack Pseudocaranx dentex (Mori et al 1992), Japanese flounder Paralichthys olivaceus (Nishizawa et al 1995), tiger puffer Takifugu rublipes, kelp grouper Epinephelus moara (Munday et al 2002) and barfin flounder Verasper moseri in Japan (Nishizawa et al 1995), and recently in golden grey mullet Liza aurata and leaping mullet Liza saliens in the Caspian Sea (Zorriehzahra et al 2016).…”
Section: Distribution and Transmissionmentioning
confidence: 96%
See 1 more Smart Citation
“…Three years later, it was recorded in European sea bass produced in Martinique (West Indies, France) and French Mediterranean (Breuil et al 1991). Since then, similar clinical signs with encephalitis associated with picorna-like viral particles were observed in the Asian sea bass Lates calcarifer cultured in Australia (Glazebrook et al 1990; Munday et al (2002) 2002), as well as in turbot Scopthalmus maximus (Bloch et al 1991), red-spotted grouper Epinephalus akaara (Nishizawa et al 1995), striped jack Pseudocaranx dentex (Mori et al 1992), Japanese flounder Paralichthys olivaceus (Nishizawa et al 1995), tiger puffer Takifugu rublipes, kelp grouper Epinephelus moara (Munday et al 2002) and barfin flounder Verasper moseri in Japan (Nishizawa et al 1995), and recently in golden grey mullet Liza aurata and leaping mullet Liza saliens in the Caspian Sea (Zorriehzahra et al 2016).…”
Section: Distribution and Transmissionmentioning
confidence: 96%
“…), and recently in golden grey mullet Liza aurata and leaping mullet Liza saliens in the Caspian Sea (Zorriehzahra et al . ).…”
Section: Distribution and Transmissionmentioning
confidence: 97%
“…It is well documented that changes experienced by ecosystems will affect the epidemiology of infectious diseases in animals, in the wild and under intensive farming conditions, including aquaculture [152][153][154][155][156]. The high number of wild asymptomatic species infected with NNV, mainly in Asian and Mediterranean countries [62,64,[66][67][68]71,80,82] and the quick rise in the viral load and subsequent outbreak of mortalities observed in experimentally infected sole when water temperature increased from 16 to 22 • C [148], suggest that VER outbreaks could have dramatic effects on natural populations, as has already been reported for some endangered fish species in the Mediterranean [72,96,109]. On the other hand, it could be argued that ocean warming could decrease the pathologies associated with the BFNNV genotype.…”
Section: Viral Thermotolerancementioning
confidence: 99%
“…The neurotropism of betanodaviruses has been repeatedly demonstrated (see reviews [74,144,163]) and viral replication seems to be almost entirely restricted to nerve tissue, preferentially brain and retina [157,162,164]. Histopathological studies have demonstrated the vacuolation of nerve cells in the olfactory lobe and cerebellum (Purkinje cell layer and the underlying granule cell layer) [10,82,119,120,125,135,161,165,166]. Megalocells and small nerve cell nuclei were also infected in the preoptic area, thalamus, medulla oblongata and spinal cord, whereas only a few small nerve cells were infected in the olfactory bulb and optic tectum [57,93,109,119,158,[166][167][168].…”
Section: Routes Of Infection and Spread Through The Fish Bodymentioning
confidence: 99%
See 1 more Smart Citation